Democratizing Innovation in Organizations: Teaching Design Thinking to Non‐Designers. (14th September 2017) - Liedtka, Jeanne; Salzman, Randy; Azer, Daisy
Abstract : Designers are comfortable with ambiguity and open‐ended questions. Not so much with industry leaders and managers who decide to take a course in design thinking. Many are risk‐averse individuals fearful of failure to begin with. They need a more structured methodology if they are to feel comfortable with designerly thinking and decision‐making.